Solar parabolic dish Stirling engine system design, simulation, and thermal analysis. (15th October 2016) - Hafez, A.Z.; Soliman, Ahmed; El-Metwally, K.A.; Ismail, I.M.
Highlights: Modeling and simulation for different parabolic dish Stirling engine designs using Matlab®. The effect of solar dish design features and factors had been taken. Estimation of output power from the solar dish using Matlab®. The present analysis provides a theoretical guidance for designing and operating solar parabolic dish system. Abstract: Modeling and simulation for different parabolic dish Stirling engine designs have been carried out using Matlab®. The effect of solar dish design features and factors such as material of the reflector concentrators, the shape of the reflector concentrators and the receiver, solar radiation at the concentrator, diameter of the parabolic dish concentrator, sizing the aperture area of concentrator, focal Length of the parabolic dish, the focal point diameter, sizing the aperture area of receiver, geometric concentration ratio, and rim angle have been studied. The study provides a theoretical guidance for designing and operating solar parabolic dish Stirling engines system. At Zewail city of Science and Technology, Egypt, for a 10 kW Stirling engine; The maximum solar dish Stirling engine output power estimation is 9707 W at 12:00 PM where the maximum beam solar radiation applied in solar dish concentrator is 990 W/m 2 at 12:00 PM. The performance of engine can be improved by increasing the precision of the engine parts and the heat source efficiency. The engine performance could be further increased if a better receiver working fluid is used. We can conclude that where the best time for heating the fluid and fasting the processing, the time required to heat the receiver to reach the minimum temperature for operating the Solar-powered Stirling engine for different heat transfer fluids; this will lead to more economic solar dish systems. Power output of the solar dish system is one of the most important targets in the design that show effectiveness of the system, and this has achieved when we take into account many factors in the design of the solar dish system. One of these factors is the reflector material of the concentrator and using the results from the Matlab simulation program; where the Polymeric Film, Non Metal reflectors, with a net conversion power of more than 97.07%, still holds the conversion record than the Anod Aluminum reflectors, which has a net conversion power 85.97% with respect to the polished stainless reflectors with a net conversion power 49.52% from the 10 kW Stirling engine. Where the power output differ as 9707, 4952, 8597 W, respectively from the 10 kW Stirling engine. It is shown that there are changes in Stirling power output for different materials, which guide us to select the optimum material, based on the targeted power output and cost. Our target to reach the optimum power that we need it in the design 10 kW power output design as an example from the solar dish Stirling engine.